sebuah - Wahyuni, Sri; I Gede Suwindia; Rahmatullah; Syaiful Bahri; Siti Musawwamah (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2025)
This study examines the dynamics of patrilineal inheritance principles in Balinese and Sasak Lombok societies through a sociological-historical approach. In particular, it explores the influence of Balinese customary law into the Sasak inheritance system and its implications for women's rights from a comparative legal perspective. Using qualitative methods through field observation and in-depth interviews, the study revealed that both systems prioritized male heirs. However, there is a fundamental difference: Balinese inheritance is closely related to the Hindu system of worship (Brahmasthana), while Sasak inheritance acts as customary law that is currently contested by Islamic inheritance principles (fiqh al-mawārīṡ). The findings suggest that although Balinese influences remain visible in the Sasak cultural structure due to historical ties to the Kingdoms of Gelgel and Karangasem, increased legal awareness among Sasak Muslim women has triggered a shift. Unlike in Bali, where inheritance is religiously binding, Sasak people increasingly negotiate the teaching by giving women a specific portion of the inheritance. This study argues that the practice of Sasak inheritance represents a dialectical space in which 'urf (custom) and sharia are in constant negotiation.